2020
DOI: 10.1186/s13048-020-00714-8
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian metastasis from nongynecologic primary sites: a retrospective analysis of 177 cases and 13-year experience

Abstract: Background Metastasis to the ovary from nongynecologic organs accounts for 9% of all ovarian malignancies. Although the most common nongynecologic primary site of ovarian metastasis is the gastrointestinal tract, metastasis from other sites to the ovary is not uncommon. Differential diagnosis of primary and metastatic ovarian tumors is important; otherwise, appropriate treatment cannot be determined. Furthermore, an optimal treatment strategy for ovarian metastasis from nongynecologic primary sites still needs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
0
16
0
1
Order By: Relevance
“…Despite the low overall rate of POCs, in those with a history of breast cancer presenting with a suspicious adnexal mass this was as high as 64%. A recent study that included one hundred and seventy-seven patients with ovarian metastasis from non-gynecological primary sites found that the colorectum (n=68) and stomach (n=61) were the two most common non-gynecological primary sites of ovarian metastasis ( 8 ). These authors also reported that more than 70% of synchronous ovarian metastases were misdiagnosed as POC prior to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the low overall rate of POCs, in those with a history of breast cancer presenting with a suspicious adnexal mass this was as high as 64%. A recent study that included one hundred and seventy-seven patients with ovarian metastasis from non-gynecological primary sites found that the colorectum (n=68) and stomach (n=61) were the two most common non-gynecological primary sites of ovarian metastasis ( 8 ). These authors also reported that more than 70% of synchronous ovarian metastases were misdiagnosed as POC prior to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Вторичные опухоли яичников составляют примерно 10-30% всех злокачественных новообразований яичников [53]. Наиболее распространенной первичной локализацией в генитальной области являются тело и шейка матки, а негенитальные первичные опухоли происходят преимущественно из желудочно-кишечного тракта (толстая кишка, аппендикс) и молочной железы, включая опухоли Крукенберга [54].…”
Section: метастатические опухоли яичников и лимфомаunclassified
“…It is worth noting that stomach is the most common nongynecologic primary site of ovarian metastasis. 13 These led us to be interested in whether estrogen promotes peritoneal metastasis of gastric cancer. Sunyi Lee et al found that estrogen aggravates tumor growth in a diffuse gastric cancer xenograft model.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the incidence rate of gastric cancer is higher in males than in females. It is worth noting that stomach is the most common nongynecologic primary site of ovarian metastasis 13 . These led us to be interested in whether estrogen promotes peritoneal metastasis of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%